Implementasi Modul Ajar Muhadatsah Al-A'rabiyyah Al-Yaumiyyah untuk Optimalisasi Pembelajaran Bahasa Arab di Madrasah Diniyyah Al-Hidayah Malang - Setiyono, Ahmad; Ardya, Nikianaku Seisagita; Intang, Nur Halisha; Renitasari, Yuli; Gina, Ayu Caesar; Andini, Faradila Ghinantia; Nabilah, Laila Janisa; Adilah, Nurul; Sidiqy, Amelia; Jayantika, Febria; Saputri, Dwi Rudita; Fairushofiddina Haq, Khusnamelda (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Arabic language education in Indonesia continues to encounter significant challenges, including diminished student engagement, temporal constraints, and insufficient instructional media. At MTS Al-Hidayah, students experience difficulties comprehending pedagogical materials that inadequately address their learning requirements, consequently resulting in reduced academic motivation. This community service initiative developed the Muhadatsah Al-'Arabiyyah Al-Yaumiyyah instructional module at Madrasah Diniyyah Al-Hidayah Malang to enhance oral proficiency through daily conversational materials, vocabulary acquisition, practice exercises, and QR-coded video learning resources. The methodology encompasses design, implementation, evaluation, and revision phases. Findings demonstrate increased student motivation and self-confidence levels. The module effectively addresses vocabulary limitations and temporal constraints through autonomous practice strategies utilizing audio-visual recordings.